Response of radial growth of Dahurian larch (Larix gmelinii) to climate factors at different altitudes in the northern part of the Greater Khingan Mountains - Luo, Taoran; Wang, Zhaopeng; Zhang, Dongyou; Li, Xiangyou; Wang, Xinrui (Frontiers in Forests and Global Change, 2024)
To investigate the differences in the response of radial growth of larch (Larix gmelinii) at varying altitude gradients to climatic factors, this study established tree-ring width chronologies of Larix gmelinii at altitudes of 900 m, 1120 m and 1300 m based dendroclimatology. We also employed R packages including "dplR", "static" and "moving" to determine the correlation between larch at different altitudes and climatic factors and to explore the sensitivity and stability between radial growth and the climate of larch at different altitudes in the northern part of the Greater Khingan Mountains Range in Northeast China.The results revealed the radial growth of larch in high altitude areas to exhibit a downward trend due to climate warming,while the growth of trees in intermediate and low altitude areas showed an upward trend. The growth-climate relationship exhibited a significant negative correlation between radial growth in low altitude larch (900 m) and temperatures in the current winter (February and March) and growing season (July, October of the current year, and October of the previous year) (p < 0.05). Moreover, high altitude larch (1300 m) showed a significant negative correlation with temperature in January, March, and October of the current year (p < 0.05).However, in intermediate altitude areas (1120 m),the radial growth of trees was significantly positively correlated with the temperature of the growing season (May, June and August). Precipitation in April was observed to promote the radial growth of low-altitude larch. Moving correlation analysis revealed that the inhibitory effect of low temperatures in winter and high temperatures in the growing season on the radial growth of larch at three altitudes gradually strengthened, transitioning from significant negative/positive correlations to significant positive/negative correlations along the altitudinal gradient.Larch trees in high and low altitudes exhibited an increased sensitivity to winter and spring precipitation, while in the intermediate region, the inhibitory effect of growing season precipitation on larch 2 radial growth continued to intensify. The results of the study have an important reference value for the in-depth understanding of the growth dynamics of Larix gmelinii natural forests in the northern part of the Greater Khingan Mountains under climate change.